A Predictive Model for Respiratory Failure and Risk Factors of Prolonged Mechanical Ventilation in Children with Guillain-Barre Syndrome - Barzegar, Mohammad; Toopchizadeh, Vahideh; Golalizadeh, Diena; Pirani, Ali; Jahanjoo, Fatemeh (Iranian Journal of Child Neurology, 2020)
Objective: Determining the predictors of respiratory failure and duration of intubation in children with Guillain-Barre Syndrome (GBS). Material and methods: Children diagnosed with GBS at Tabriz Children’s Hospital were studied. Factors associated and influencing respiratory failure and duration of intubation were determined using both univariate and multiple analysis. Results: Three hundred twenty-four children were enrolled in the study, of whom 54.0% were males. Thirty-one (9.6%) patients underwent mechanical ventilation, the patients under 5 years old were more prone to requirement of mechanical ventilation (11.3% vs. 6.9%). The cases who are hospitalized in winter were more likely to need ventilation compared to the cases hospitalized in the spring (OR =7.00 ; 95% CI:1.51 - 32.53 ). Also autonomic involvement (OR= 8.88 ,95% CI :4.03 - 19.58 ,p<0.001) and cranial nerves involvement (OR =9.88 ,95% CI:3.68 - 26.52, p<0.001) emerged as risk factors for mechanical ventilation requirement. Overall, 16.1% of patients with axonal electrophysiologic pattern required mechanical ventilation compared to 7.4% among those with demyelinating type, (OR:2.15, 95% CI: 1.01 - 4.69). In univariate analysis, the only variable which has a correlation with the duration of intubation is axonal electrophysiologic pattern p= 0.028. Conclusion: Approximately 10% of patients required mechanical ventilation. Season, cranial nerve involvement, autonomic dysfunction, and the electrophysiologic pattern is more important variables for prediction and duration of respiratory failure and mechanical ventilation.